Clinical Significance of Myeloid‐Derived Suppressor Cells in Human Immunodeficiency Virus‐1/ Hepatitis C Virus‐coinfected Patients. (June 2016) - Lei, A. H.; Yang, Q.; Cai, W. P.; Liu, Y. F.; Lan, Y.; Qin, A. P.; Hu, F. Y.; Zhou, J.
Abstract: Myeloid‐derived suppressor cells (MDSCs) are known to accumulate during chronic viral infection, including human immunodeficiency virus‐1 (HIV‐1) and hepatitis C virus (HCV) infection, and play a critical role in suppressing immune responses. However, the role of MDSCs in HIV/HCV coinfection is unclear. Here, we observed a dramatic increase in monocytic MDSCs (M‐MDSCs) level in the peripheral blood of HIV/HCV‐coinfected patients compared to that of healthy controls; the level of M‐MDSCs proportion in coinfection was not higher than that in HIV or HCV monoinfection. Interestingly, we found the M‐MDSCs level in coinfected patients correlated well with CD4 + T cell loss ( r = −0.5680; P = 0.0058), HIV‐1 load ( r = 0.6011; P = 0.0031), HCV load ( r = 0.6288; P = 0.0017) and activated CD38 + T cells ( r = 0.5139; P = 0.0144). Initiation of highly active antiretroviral therapy considerably reduced both M‐MDSCs and CD8 + CD38 + ‐activated T cell proportion in coinfected patients, and they showed a parallel course of decline. Thus, our results suggest that HIV‐1 infection and high chronic immune activation may contribute to the expansion of M‐MDSCs and accelerate the disease progression in HIV/HCV‐coinfected patients.